Formal remediation and probation (part 2 of 3). When residents shouldn’t become clinicians: getting a grip on fair and defensible processes for termination of training - Schultz, Karen; Risk, Andrea; Newton, Lisa; Snider, Nicholas (Canadian Medical Education Journal, 2021)
Training programs have the dual responsibility of providing excellent training for their learners and ensuring their graduates are competent practitioners. Despite everyone’s best efforts a small minority of learners will be unable to achieve competence and cannot graduate. Unfortunately, program decisions for training termination are often overturned, not because the academic decision was wrong, but because fair assessment processes were not implemented or followed. This series of three articles, intended for those setting residency program assessment policies and procedures, outlines recommendations, from establishing robust assessment foundations and the beginning of concerns (Part One), to established concerns and formal remediation (Part Two) to participating in formal appeals and after (Part Three). With these 14 recommendations on how to get a grip on fair and defensible processes for termination of training, career-impacting decisions that are both fair for the learner and defensible for programs are indeed possible. They are offered to minimize the chances of academic decisions being overturned, an outcome which wastes program resources, poses patient safety risks, and delays the resident finding a more appropriate career path. This article (Part Two in the series of three) will focus on what to do when concerns become established, and a formal remediation or probation is necessary.